COMPARATIVE ANALYSIS OF PHRASEOLOGICAL UNITS IN COGNITIVE ASPECT (Conferencea, 2023)
At the present stage, the high level of development of phraseology and the growing interest in colloquial vocabulary, which manifests itself in the fiction of modern authors, in periodicals and feature films, determines the relevance of comparing languages, identifying their similarities and differences in certain aspects. The comparative study of phraseological systems of different languages is of great importance both for the development of a general theory of phraseology and for the study of the common and distinctive features of the languages under study. The relevance and growing role of the comparative study of phraseology is confirmed by a large number of research works in this area. The purpose of this article is a comprehensive study and comparative analysis of the features of phraseological units with adjectives denoting a person’s character based on cognitive aspect.